Evidence-Based Approaches to Glaucoma Management During Pregnancy and Lactation - Drake, Susie C. (Curr Ophthalmol Rep, 2016)
With increasing maternal age in this decade, there is a parallel rise in the number of pregnant and lactating women affected by glaucoma worldwide. Understanding the diagnosis and management of glaucoma during pregnancy and lactation is essential to preventing blindness from glaucoma in this vulnerable population. This report provides a review of the current literature and offers effective strategies that will overcome the challenges in managing glaucoma during pregnancy and lactation. Practically, glaucoma management during pregnancy and lactation presents a unique challenge for the physician, as the benefit of any treatment must be weighed against the potential risks to the fetus. Prior to initiating or continuing treatment, the physician should be familiar with the various treatment options to manage intraocular pressure during pregnancy and lactation, including the safety of various anti-glaucoma medications as supported by the existing literature and based on the food and drug administration guidelines. A collaborative team effort between the ophthalmologist, obstetrician, and neonatologist in high-risk pregnancies is recommended to optimize care for the mother and fetus.